Evaluation of human chorionic gonadotropin as a replacement for GnRH in an ovulation synchronization protocol before fixed-time insemination - M.G. Burns; B.S. Buttrey; D.R. Eborn; J.E. Larson; B.J. Lovaas; G.C. Lamb; Jeffrey S. Stevenson; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2007)
Two experiments were conducted to evaluate the difference between gonadotropinreleasing hormone (GnRH) and human chorionic gonadotropin (hCG) given at the beginning of a timed AI protocol and their effects on fertility. In Experiment 1, beef cows (n = 672) at six different locations were assigned randomly to treatments based on age, body condition, and days postpartum. On day −10, cattle were treated with GnRH or hCG and a progesterone-releasing controlled internal drug release (CIDR) insert was placed in the vagina. An injection of PGF2αwas given and CIDR inserts were removed on day −3. Cows were inseminated at one fixed timed at 62 hr (day 0) after CIDR insert removal. Pregnancy was diagnosed at 33 days (range of 32 to 35) after insemination to determine pregnancy rates. For cows that were pregnant after the first insemination, a second pregnancy diagnosis was conducted 35 days (range of 33 to 37) after the first diagnosis to determine pregnancy survival. Pregnancy rates were reduced by the hCG injection compared with the GnRH injection (39.1 vs. 53.5%). In Experiment 2, cattle were assigned randomly to three treatments, balanced evenly across the two treatments (GnRH vs. hCG) applied in Experiment 1. Cows were injected with GnRH, hCG, or saline seven days before the first pregnancy diagnosis of cows inseminated in Experiment 1. At the time of pregnancy diagnosis, cattle found not pregnant (n = 328) were given PGF2αand inseminated 56 hours later. A second pregnancy diagnosis was conducted 35 days (range of 33 to 37) after the second insemination to determine pregnancy rate at the second AI. Injections of GnRH, hCG, or saline had no effect on pregnancy rates of cows already pregnant to the first insemination. Pregnancy rates after second insemination in cows given an injection of hCG or GnRH, however, tended to be reduced. Percentage of cows pregnant after two timed inseminations exceeded 60% without any need to detect estrus.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Gonadotropin releasing hormone (GnRH); CIDR; Ovulation